Allelic variation at the C-reactive protein gene associates to both hand osteoarthritis severity and serum high sensitive C-reactive protein levels in the GARP study. Issue 6 (29th November 2007) - Bos, S D; Suchiman, H E D; Kloppenburg, M; Houwing-Duistermaat, J J; Hellio le Graverand, M P; Seymour, A B; Kroon, H M; Slagboom, P E; Meulenbelt, I
Abstract : Objective: To gain more insight into the role of genetic variation of the C-reactive protein (CRP) gene in serum CRP levels and osteoarthritis (OA). Methods: Serum high sensitive CRP (S-HsCRP) levels were measured in the Genetics of osteoARthritis and Progression (GARP) study. Furthermore, to assess genetic variation of the CRP gene, genotypes of five tagging single nucleotide polymorphisms were assessed in the GARP study and a random control sample. Results: A significant and consistent relation between S-HsCRP levels and observed haplotypes was identified. Additionally, a CRP haplotype, which also associated to a significantly higher expected phenotypic mean S-HsCRP level, was associated to severe hand OA. This haplotype was tagged by a single nucleotide polymorphism (rs3091244). Carriers of this allele have an increased risk for the presence of severe hand OA with an OR of 2.3 (95% confidence interval 1.2 to 4.3, p = 0.009). Conclusions: A haplotype of the CRP gene, associated to high basal S-HsCRP level, is also associated to severity of hand OA, indicating that innate high basal S-HsCRP levels may influence OA onset.